Extraterrestrial dust as a source of bioavailable iron contributing to the ocean for driving primary productivity. (24th November 2021) - Rudraswami, N. G.; Pandey, M.; Genge, M. J.; Fernandes, D.
Abstract: Bioavailable Fe is an essential nutrient for phytoplankton that enables the organisms to flourish and draw down atmospheric CO2 thus affecting global climatic conditions. In marine locales, remote from the continents, extraterrestrial dust provides an important source of Fe and thus moderates primary productivity. Here, we provide constraints on partitioning of extraterrestrial Fe between seawater and sediments from the observations of dissolution and the alteration of cosmic spherules recovered from deep‐sea sediments and Antarctica. Of the ∼3000–14, 000 t a −1 extraterrestrial dust that reaches Earth's surface, ∼2–5% material falling in the oceans survives in marine sediments while the remainder is liberated into seawater. Both processes contribute ∼(3–10) × 10 −8 mol Fe m −2 yr −1 . The Fe contribution of surviving particles due to etching is estimated to be ∼10% of Fe contribution of meteoric smoke. Changes in extraterrestrial dust flux over geological time scales not only vary Fe delivery to the oceans by up to three orders of magnitude but also the partitioning of Fe between surface and abyssal waters depending on entry velocity and evaporation.